Penyelesaian Perselisihan Hubungan Industrial Melalui Mediasi Di Kecamatan Tembilahan - Yola Afia Masdar; Nurmasari Nurmasari (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2019)
This study aims to determine and analyze the Implementation of Industrial Relations Duties and Job Conditions by the Department of Manpower and Transmigration in Tembilahan District (Case Study of Industrial Relations Dispute Resolution Through Mediation). Indicators for evaluating the implementation of tasks used include Industrial Relations Development, Industrial Relations Development, and Settlement of Industrial Relations Disputes Outside the Court. This type of research is a descriptive survey with quantitative analysis, which prioritizes the questionnaire list as a means of collecting data and data collected with this tool and then becomes the main raw material for analyzing empirical conditions and objectivity of the existence of objectives at the study site. The population and sample in this study were 20 people. The types and data collection techniques used consisted of, primary data collected using questionnaire list techniques and interviews and secondary data collected using observation techniques. While the data analysis technique used is to use a score technique. Based on this analysis technique, the researcher assessed and concluded the research was categorized as sufficiently implemented. The inhibiting factor is the lack of budget in fulfilling the needs of the mediation process, both in terms of mediator human resources needed, as well as in terms of facilities and infrastructures including supporting soundproof rooms and recorders. So that the work becomes less implemented with a maximum.